2014
DOI: 10.1017/s1463423614000279
|View full text |Cite
|
Sign up to set email alerts
|

Talk weight: an observational study of communication about patient weight in primary care consultations

Abstract: BackgroundObesity is a major public health issue and primary care practitioners are well placed to opportunistically raise the issue of overweight or obesity with their patients.Aim and methodsThis study investigated the prevalence of weight discussion in primary care consultations with overweight and obese patients, in a practice in Fife, Scotland, and described weight-related communication using video analysis.FindingsWeight was raised in 25% of consultations with overweight and obese patients. GPs initiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 26 publications
2
41
1
4
Order By: Relevance
“…Given their frequent contact with patients who are considered overweight or obese (Heintze et al, ; Laidlaw, McHale, Locke, & Cecil, ; Peters et al, ; Swift, Choi, Puhl, & Glazebrook, ), primary health care physicians (GPs in Australia) are often identified in dominant discourse as the central actors in responding to rates of overweight and obesity (Heintze et al, ; Laidlaw et al, ; Peters et al, ). Consequently, GPs increasingly receive explicit directives from overseeing bodies to work intensively with patients around overweight and obesity (Alexander et al, ; Laidlaw et al, ). However, currently available evidence suggests that discussions about overweight and obesity between a patient and their primary health care professional are uncommon (Turner, Harris, & Mazza, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given their frequent contact with patients who are considered overweight or obese (Heintze et al, ; Laidlaw, McHale, Locke, & Cecil, ; Peters et al, ; Swift, Choi, Puhl, & Glazebrook, ), primary health care physicians (GPs in Australia) are often identified in dominant discourse as the central actors in responding to rates of overweight and obesity (Heintze et al, ; Laidlaw et al, ; Peters et al, ). Consequently, GPs increasingly receive explicit directives from overseeing bodies to work intensively with patients around overweight and obesity (Alexander et al, ; Laidlaw et al, ). However, currently available evidence suggests that discussions about overweight and obesity between a patient and their primary health care professional are uncommon (Turner, Harris, & Mazza, ).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that patients have often been found to be reticent about bringing up their weight with doctors (Tham & Young, ; Thomas, Hyde, Karunaratne, Herbert, & Komesaroff, ). GPs in Laidlaw et al’s (, p. 313) study were more likely to initiate a discussion about weight than patients, but these discussions were rarely successful and patients frequently “reduced space” (defined by Laidlaw et al (, p. 311) as “using behaviours that are not facilitative for discussing weight, such as blocking or reducing scope for further discussion or changing the topic of discussion”) for these conversations. Patient‐initiated discussions were “more likely to result in a weight‐related outcome” (Laidlaw et al, , p. 313).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poised in this vital position therefore, GPs are not only ideally placed, but entrusted by best practice to measure obesity predictors, diagnose obesity and monitor progress [2, 5]. Laidlaw et al (2015) reported that although GPs initiated weight discussions more often than patients did, their attempts were often blocked by the patients [6]. …”
Section: Main Textmentioning
confidence: 99%